Etiology and functional validation of gastrointestinal motility dysfunction in a zebrafish model of CHARGE syndrome. (27th April 2018) - Cloney, Kellie; Steele, Shelby L.; Stoyek, Matthew R.; Croll, Roger P.; Smith, Frank M.; Prykhozhij, Sergey V.; Brown, Mary M.; Midgen, Craig; Blake, Kim; Berman, Jason N.
Abstract : CHARGE syndrome is linked to autosomal‐dominant mutations in the CHD7 gene and results in a number of physiological and structural abnormalities, including heart defects, hearing and vision loss, and gastrointestinal (GI) problems. Of these challenges, GI problems have a profound impact throughout an individual's life, resulting in increased morbidity and mortality. A homolog of CHD7 has been identified in the zebrafish, the loss of which recapitulates many of the features of the human disease. Using a morpholino chd7 knockdown model complemented by a chd7 null mutant zebrafish line, we examined GI structure, innervation, and motility in larval zebrafish. Loss of chd7 resulted in physically smaller GI tracts with normal epithelial and muscular histology, but decreased and disorganized vagal projections, particularly in the foregut. chd7 morphant larvae had significantly less ability to empty their GI tract of gavaged fluorescent beads, and this condition was only minimally improved by the prokinetic agents, domperidone and erythromycin, in keeping with mixed responses to these agents in patients with CHARGE syndrome. The conserved genetics and transparency of the zebrafish have provided new insights into the consequences of chd7 gene dysfunction on the GI system and cranial nerve patterning. These findings highlight the opportunity of the zebrafish to serve as a preclinical model for studying compounds that may improve GI motility in individuals with CHARGE syndrome. Abstract : A larval zebrafish model of CHARGE syndrome was gavage‐fed fluorescent green beads and the passage of the beads through the intestine was monitored for 24 h. Compared to normal larvae, these CHARGE fish were less able to pass the beads from their intestines. This suggests that intestinal motility is impaired in these fish and likely in individuals with CHARGE.